3D ultra-high resolution seismic imaging of shallow Solfatara crater in Campi Flegrei (Italy): New insights on deep hydrothermal fluid circulation processes - Grazia De Landro (Nature Portfolio, 2017)
Abstract Seismic tomography can be used to image the spatial variation of rock properties within complex geological media such as volcanoes. Solfatara is a volcano located within the Campi Flegrei, a still active caldera, so it is of major importance to characterize its level of activity and potential danger. In this light, a 3D tomographic high-resolution P-wave velocity image of the shallow central part of Solfatara crater is obtained using first arrival times and a multiscale approach. The retrieved images, integrated with the resistivity section and temperature and the CO2 flux measurements, define the following characteristics: 1. A depth-dependent P-wave velocity layer down to 14 m, with Vp < 700 m/s typical of poorly-consolidated tephra and affected by CO2 degassing; 2. An intermediate layer, deepening towards the mineralized liquid-saturated area (Fangaia), interpreted as permeable deposits saturated with condensed water; 3. A deep, confined high velocity anomaly associated with a CO 2 reservoir. These features are expression of an area located between the Fangaia, water saturated and replenished from deep aquifers, and the main fumaroles, superficial relief of the deep rising CO2 flux. Therefore, the changes in the outgassing rate greatly affect the shallow hydrothermal system, which can be used as a “mirror” of fluid migration processes occurring at depth.